2018
DOI: 10.1111/1750-3841.14346
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum CQPC06 Activity Prevents Dextran Sulfate Sodium‐Induced Colitis by Regulating the IL‐8 Pathway

Abstract: In this study, a newly discovered lactic acid bacteria was investigated. This bacterial strain had a good prophylactic effect against colitis in a mouse model, and might have potential utility as a probiotic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…UC can lead to bloody diarrhea, rectal bleeding, unintended weight loss, and other symptoms. DAI can be used as a standard to measure the severity of UC (Zhang et al., 2018). DAI analysis revealed that LP‐YS3 could decrease the symptoms of DSS‐induced UC, and this effect was more evident with an increase in LP‐YS3 concentration.…”
Section: Discussionmentioning
confidence: 99%
“…UC can lead to bloody diarrhea, rectal bleeding, unintended weight loss, and other symptoms. DAI can be used as a standard to measure the severity of UC (Zhang et al., 2018). DAI analysis revealed that LP‐YS3 could decrease the symptoms of DSS‐induced UC, and this effect was more evident with an increase in LP‐YS3 concentration.…”
Section: Discussionmentioning
confidence: 99%
“…HT-29 cells produce IL-8 after stimulation by TNF-α and IL-1β, but not by IFN-γ, IL-10 or IL-13 [11]. TNF-α plays a guiding role in the production of IL-8, and NF-κB establishes a feedback mechanism via autocrine/paracrine factors to regulate the expression and activation of IL-8 [42].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mucus is important for the lubrication and protection of the intestinal epithelium from toxic substances coming from the external environment, such as DSS (Abrantes et al, 2020). Thus, in mouse colon inflammation caused by DSS intake, it is common to observe a decrease in goblet cell number, but it can be restored by the consumption of probiotic bacteria (Rodrigues et al, 2018;Zhang et al, 2018;Abrantes et al, 2020). It is important to highlight that MUC-2 is the major glycoprotein constituent of intestinal mucus and is secreted primarily by goblet cells (Perez-Vilar, 2007).…”
Section: Discussionmentioning
confidence: 99%